2004
DOI: 10.1037/0096-1523.30.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Balancing Space and Time in Memory: Tau and Kappa Effects Revisited.

Abstract: In 3 experiments, the authors studied the organization of spatiotemporal information in memory. Stimuli consisted of configurations of dots, presented sequentially. The stimuli were either proportional, with interdot distances corresponding to interdot durations, or not proportional, with interdot distances not corresponding to interdot durations. After a learning phase, participants reproduced the spatial (Experiment 1), temporal (Experiment 2), or spatial and temporal (Experiment 3) characteristics of the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 58 publications
4
68
1
Order By: Relevance
“…For example, it has been shown that distance judgments of visual stimuli vary depending on temporal inter-stimulus intervals (Benussi 1913) and that duration judgments are influenced by the spatial dimensions of presented stimuli (Abe 1935;see also Collyer 1977). This dependence between spatial and temporal codes was recently corroborated by Casasanto and Boroditsky (2008), who observed that their participants were unable to ignore irrelevant spatial information while performing duration judgments (see also Sarrazin et al 2004, for an overview). Moreover, Vallesi et al (2008) reported an interaction of foreperiod duration (i.e., the interval from the start of a warning signal until the presentation of an imperative stimulus) and response hand.…”
Section: Introductionmentioning
confidence: 58%
“…For example, it has been shown that distance judgments of visual stimuli vary depending on temporal inter-stimulus intervals (Benussi 1913) and that duration judgments are influenced by the spatial dimensions of presented stimuli (Abe 1935;see also Collyer 1977). This dependence between spatial and temporal codes was recently corroborated by Casasanto and Boroditsky (2008), who observed that their participants were unable to ignore irrelevant spatial information while performing duration judgments (see also Sarrazin et al 2004, for an overview). Moreover, Vallesi et al (2008) reported an interaction of foreperiod duration (i.e., the interval from the start of a warning signal until the presentation of an imperative stimulus) and response hand.…”
Section: Introductionmentioning
confidence: 58%
“…Over the past century of psychophysical experimentation on space and time judgments, two effects have been demonstrated repeatedly: the Kappa effect and the Tau effect (Benussi, 1913;Bill & Teft, 1969;Cohen, 1967;Cohen et al, 1954;Collyer, 1977;Helson, 1930;Jones & Huang, 1982;Price-Williams, 1954;Sarrazin et al, 2004). In a typical experiment, three light bulbs were arranged in a row and flashed in succession, forming two spatiotemporal intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Is the way we think about time dependent on space even when we're not using language at all? Previous research on the experience of distance and duration has shown that the two are not independent (Benussi, 1913;Bill & Teft, 1969;Cohen, 1967;Cohen, Hansel, & Sylvester, 1954;Collyer, 1977;Helson, 1930;Jones & Huang, 1982;Price-Williams, 1954;Sarrazin, Giraudo, Pailhous, & Bootsma, 2004), but little is known about whether the relationship between the two domains is asymmetrical, in the way that has been observed in language. The purpose of the present study is to test whether the asymmetrical dependence of time on space exists even at a more basic level of the human conceptual system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kappa effect in the auditory mode was investigated in the present study. The kappa effect has been tested more often in the visual mode (Cohen, Hansel, & Sylvester, 1953Collyer, 1977;Miyatani, 1984Miyatani, -1985Sarrazin, Giraudo, Pailhous, & Bootsma, 2004), and even in the tactile mode (Goldreich, 2007;Suto, 1952Suto, , 1955Suto, , 1957. There are researches testing the kappa effect in the auditory mode, but most of them focused on the effects of frequency distance (difference), instead of spatial distance, on the perception of time duration (Cohen, Hansel, & Sylvester, 1954;Jones & Huang, 1982;Shigeno, 1986;Yoblick & Salvendy, 1970).…”
Section: Introductionmentioning
confidence: 99%